Contact pathway in surgical and transcatheter aortic valve replacement - de la Morena-Barrio, María Eugenia; Corral, Javier; López-García, Cecilia; Jiménez-Díaz, Víctor Alonso; Miñano, Antonia; Juan-Salvadores, Pablo; Esteve-Pastor, María Asunción; Baz-Alonso, José Antonio; Rubio, Ana María; Sarabia-Tirado, Francisco; García-Navarro, Miguel; García-Lara, Juan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Aortic valve replacement is the gold standard treatment for severe symptomatic aortic stenosis, but thrombosis of bioprosthetic valves (PVT) remains a concern. Objective: To analyse the factors involved in the contact pathway during aortic valve replacement and to assess their impact on the development of thromboembolic complications. Methods: The study was done in 232 consecutive patients who underwent: transcatheter aortic valve replacements (TAVR, N=155), and surgical valve replacement (SAVR, N=77) (MUVITAVI project). Demographics and clinical data, outcomes including a combined end point (CEP) of thrombotic events, and imaging controls were recruited. Samples were collected 24 hours before and 48 hours after valve replacement. FXII, FXI and (pre)kallikrein were evaluated by Western Blot and specific ELISA with nanobodies. Results: The CEP of thrombotic events was achieved by 19 patients: 13 patients presented with systemic embolic events and 6 patients with subclinical PVT. There was neither FXII activation nor generation of kallikrein. There was a significant reduction of FXI levels associated with the procedure, which was statistically more pronounced in SAVR than in TAVR. Cases with reductions of FXI below 80% of basal values had lower incidence of embolic events during the procedure than patients in whom FXI increased above 150%: 2.7% vs 16.7%; p: 0.04. Conclusions: No activation of the contact pathway was caused by TAVR or SAVR. A significant reduction of FXI, was observed, particularly in SAVR, associated with lower incidence of thrombotic events. These results encourage evaluating the usefulness and safety of antithrombotic treatments targeting FXI in these patients.